David Lynch, os Puzzle films e o cinema limítrofe: uma análise do filme cidade dos sonhos - SOSA MÉROLA, Alicia Margarita (2017)
This dissertation proposes an analysis of the film Mulholland Drive, 2001 by the North American director David Lynch, a work that presents a complex and non-linear narrative. Based on the concept of borderline cinema it is observed how Lynch constructs such narrative complexity, which is also close to surrealist cinema, because such a narrative structure resembles a certain dream logic. The concept of borderline cinema, according to Rogério Ferraraz (2003), is found in the borders of illusionism and anti-illusionism, of the film of gender and the experimental film. In order to understand this borderline cinema, a study of the theories of film narrative was placed, ranging from classical narration to avant-garde proposals. In this context, we used David Bordwell's (1996) studies on film narrative that are associated with the cognitive analytic tradition of contemporary film studies. The presence of the complex narrative, among other characteristics discussed in this research, allows Mulholland Drive to be classified as a puzzle movie, according to studies by Warren Buckland (2009). However, if the film analysis of Mulholland Drive allowed, on one hand, a survey of the characteristics that corroborate both the concept of borderline cinema and the puzzle film, establishing a dialogue between these two themes, on the other hand, it was possible to perceive that Lynch's work differs from other puzzle films raised by Buckland.